PELATIHAN PEMBUATAN PAKAN MENGGUNAKAN BAHAN BAKU LOKAL PADA KELOMPOK BUDIDAYA UDANG VANAME (Litopanaeus vanname) DI DESA TUADA HALMAHERA BARAT - Rovina Andriani; Fatma Muchdar; Muhammad Irfan; Juharni Juharni; Ikbal Marus; Syahnul Sardi Titaheluw (Jurnal Abdi Insani, 2022)
The fishing business system that has been carried out in Tuada Village is in two ways, namely sea fishermen and pond cultivators. The types of cultivation that are carried out are the cultivation of tilapia, milkfish and vannamei shrimp (Litopenaeus vanname). In intensive fish/shrimp farming, around 70% of production costs are used to purchase feed, where commercial feed prices continue to increase. Therefore, proper formulation of fish feed using local raw materials can reduce production costs and increase farmer profits. The purpose of this community service activity is to increase community knowledge, especially the fish/shrimp cultivating community in Tuada Village, in the process of making fish/shrimp feed and management of fish/shrimp feeding. This training activity was held in August 2022, taking place at the Tuada Village office which involved the community and KKN students at Khairun University. The method used is in the form of understanding the theory of feed management, introduction of materials and tools as well as training in making feed according to the formulation. Training activities start with the presentation of feed manufacturing theory and feed manufacturing technology with the distribution of practical modules to participants to make it easier to understand the theory conveyed by resource persons, then an introduction to feed raw materials, preparation of tools and training materials covering what tools are used in the feed manufacturing process, the process mixing of feed ingredients at this stage is a concern because if the ingredients are not mixed well (homogeneous) then the quality of the feed produced is not as expected, finally, the feed molding process uses a meat grinder with a production capacity of ± 3-5 kg ​​of feed per day. Making shrimp feed can be done by the community easily. The manufacturing stage starts from the introduction of raw materials, the tools used, the process of mixing and printing feed.